WA40 The good neighbour partnership: why do we need it? who is going to do it? how on earth are we going to evaluate it?. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - McLoughlin, Kathleen; Rhatigan, Jim; McGilloway, Sinead; Callinan, Joanne; Wright, Marie; Kellehear, Allan; Lucey, Michael; Conroy, Marian; Twomey, Feargal; Kumar, Suresh; Herrera-Mollina, Emillio; Furlong, Mairead; et al.
Abstract : This one-hour symposium considers Milford Care Centre's Compassionate Communities Good Neighbour Partnership and it's evaluation by an international team, led by Maynooth University and funded by the All Ireland Institute of Hospice and Palliative Care, The Irish Cancer Society, The Irish Hospice Foundation and Milford Care Centre. The symposium will be divided into three sections: 1. The Good Neighbour Partnership: Why do we need it? In this section we will describe the findings from a recent scoping study to determine the social and practical needs of community dwelling adults (and their families) living with advanced life limiting illness at home. We will consider the rationale for specialist palliative care services, working with community groups, to lead the development of a volunteer-based social model of care to address unmet need. 2. The Good Neighbour Partnership: How do we recruit and train volunteers? We will share our process and experience of recruiting and training 15 Compassionate Communities Volunteers to assess unmet social and practical need, and to mobile the person's circle of community to meet those needs. An understanding of the motivating factors of volunteers will be shared. 3. The Good Neighbour Partnership: How on earth are we going to evaluate it? Here we describe the INSPIRE study – Investigating Social and Practical Supports at the End of life. An exploratory delayed intervention randomised controlled trial (framed by the MRC Framework for Complex Interventions) to assess the feasibility, acceptability and potential effectiveness of the Good Neighbour Partnership.